Role of Urokinase Receptor and Caveolin in Regulation of Integrin Signaling - Chapman, Harold A.; Wei, Ying; Simon, Daniel I.; Waltz, David A. (Thrombosis and Haemostasis, 1999)
Integrins are a group of heterodimeric adhesion receptors that mediate attachment of cells to extracellular matrices and other cells. These receptors serve as a major site of information flow from the immediate pericellular environment to the cellular interior and, in reverse, as effectors of the cellular responses to such information in biological processes as diverse as inflammation, tissue remodeling, growth, and tumorigenesis.1-3 The binding specificities of integrin receptors are determined by interactions of ligands with both the α and β chains that comprise integrins. Diversity of ligand binding is promoted by the fact that a single α chain may partner with numerous distinct β chains, and cells may express more than one and, sometimes, many α and β chains. Thus, as a family, integrins have the capacity to interact with a large set of cellular and extracellular matrix ligands. The structural features of integrin heterodimers that underlie their interactive potential and ligand specificity have been the subject of several recent reviews and will not be discussed here.4,5A fundamental feature of integrins is that their function is determined not simply by their expression on the cell surface but by their dynamic regulation through activating events that amplify, sometimes only transiently, the adhesive capacity of integrins for their counter-ligands and the signals that follow.1-3,6,7 These dynamic aspects of integrin function are dependent on integrin interactions with its neighbors in the cell membrane and inside the cell, a structural consequence of the fact that integrins contain only short cytoplasmic tails without intrinsic signaling capacity. Three major sites of dynamic regulation of integrin function, indicated schematically in Figure 1, are as follows: ligand binding, association of cytoplasmic signaling elements with integrin cytoplasmic tails, and regulation of integrin binding and signaling by association with non-integrin “membrane adaptors.” Ligand binding by integrins is a function of their conformational state (Fig. 1a). Recent molecular modeling suggests that integrin α and β chains may exist in a relatively weak binding or “inactive state,” in which α and β chains extensively overlap and the β chain obscures binding sites on the α chain.5,8 In this model “activation” of integrins results from an altered conformation in which there is less overlap and more extensive availability of binding sites for ligand engagement. Such changes in conformational state may occur as a consequence of integrin clustering (following initially weak ligand binding).The capacity of integrins to cluster and connect with the cytoskeleton (Fig. 1b) in a manner promoting adhesion and migration is also regulated by complex interactions of kinases, phosphatases, and various structural proteins that bind to and assemble around integrin cytoplasmic tails. Signals derived from G-protein-coupled chemotactic receptors or generated by engagement of integrin extracellular ligand domains and clustering promote the activation of Src-family kinases, generation of lipid mediators, and in some cases, Ca2+ transients. These membrane proximate signals initiate and then propagate the accumulation of kinases and structural proteins surrounding a cluster of integrins. These events may also, in effect, be “insideout signals” affecting the conformational state of integrin extracellular domains1 (Fig. 1a). The assembly of cytoplasmic signaling elements on or near integrin cytoplasmic tails appears fundamental to the capacity of integrins to mediate adhesion and to impart, by signaling to the cellular interior, the nature of the immediate extracellular milieu.More recently, evidence has emerged that integrin function is also regulated by non-integrin membrane proteins that associate with integrins outside or within the plasma membrane (Fig. 1c). These include the tetraspan family of membrane proteins (CD9, CD63, CD81, CD82, and others), integrin-associated protein (CD47), and CD98.9-11 In addition, we and others have previously reported that β1 integrin function is regulated by its association with the glycosylphosphatidyl-inositol (GPI)-linked non-integrin receptor, the urokinase receptor (u-PAR, CD87), and a cholesterol-binding membrane protein called caveolin.12,13 As with ligand binding, structural features of the integrin heterodimers appear to dictate their association with these different membrane adaptors. For example, CD47 is reported to specifically interact with and promote the signaling function of αv/β3.10 The tetraspan family of proteins predominantly interacts with β1 integrins, but reportedly, only with certain α chain/β1 pairs.9 The functional effects of tetraspan proteins on integrin function is uncertain, though it is remarkable that at least two of these proteins (CD81 and 82) have been reported to inhibit tumor cell motility and act as tumor suppressors.14, 15 Caveolin and u-PAR also exhibit preferences for integrin interactions. Wary et al reported α-chain specificity for the association of β1 integrins with caveolin-1.12 The u-PAR receptor physically binds to the purified β2 integrin Mac-1 (CD11b/CD18), though no binding is observed in similar experiments with the β2 integrin CD11a/CD18 (LFA-1).16 Thus, like extracellular ligand interactions and intracellular cytoplasmic interactions, the capacity of integrins to interact with non-integrin membrane adaptors appears to be determined by amino acid sequences within the integrin heterodimers. The exact molecular basis for these interactions remains uncertain and is being actively investigated. This brief review will focus on the functional consequences of interaction of β1integrins with two of these membrane adaptors, u-PAR and caveolin.